Invasiveness of endometrial cancer cell lines is potentiated by estradiol and blocked by a traditional medicine Guizhi Fuling at clinically relevant doses - Khan, Sidra; Varricchio, Alanah; Ricciardelli, Carmela; Yool, Andrea J. (Frontiers in Oncology, 2023)
The Traditional Chinese medicine, Guizhi Fuling (here called Fuling), has been confirmed in meta-analysis studies to reduce recurrence of endometriosis and improve pregnancy outcomes; however, the possible use of Fuling as a fertility-preserving treatment in endometrial cancer has not previously been tested. Results here are the first to demonstrate dose-dependent inhibition of cell motility by Fuling in two endometrial cancer cell lines, classified as Grade I (Ishikawa) which is responsive to progestin treatment, and Grade III (MFE-280) which is resistant. The major outcome of this study was the novel demonstration that Fuling (30-80 µg/ml) significantly inhibits invasiveness in both high and low grades of EC cells, achieving 70-80% block of trans-barrier migration without cytotoxicity. This effective dose range is estimated to be comparable to that used in human clinical trials and traditional practice. Results here further show that clinically relevant doses of Fuling override the motility-promoting effects of estradiol in endometrial cancer cell lines. Medroxyprogesterone acetate has to date been the standard therapy to treat metastatic or inoperable endometrial cancers; however, success rates are low with high rates of recurrence, due in part to acquired resistance to medroxyprogesterone acetate therapy. The discovery here that Fuling appears to control the spread of treatment-resistant advanced cancers is an exciting prospect.